Dspp-independent Effects of Transgenic Trps1 Overexpression on Dentin Formation. (August 2015) - Mobley, C.G.; Kuzynski, M.; Zhang, H.; Jani, P.; Qin, C.; Napierala, D.
The Trps1 transcription factor is highly expressed in dental mesenchyme and preodontoblasts, while in mature, secretory odontoblasts, it is expressed at low levels. Previously, we have shown that high Trps1 levels in mature odontoblasts impair their function in vitro and in vivo. Col1a1-Trps1 transgenic (Trps1-Tg) mice demonstrate defective dentin secretion and mineralization, which are associated with significantly decreased Dspp expression due to direct repression of the Dspp gene by Trps1. Here, by crossing Trps1-Tg and Col1a1-Dspp transgenic (Dspp-Tg) mice, we generated Col1a1-Trps1;Col1a1-Dspp double transgenic (double-Tg) mice in which Dspp was restored in odontoblasts overexpressing Trps1. Comparative micro–computed tomography analyses revealed partial correction of the dentin volume and no improvement of dentin mineralization in double transgenic mice in comparison with Trps1-Tg and wild-type (WT) mice. In addition, dentin of double-Tg mice has an irregular mineralization pattern characteristic for dentin in hypophosphatemic rickets. Consistent with this phenotype, decreased levels of Phex, Vdr, and Fam20c proteins are detected in both Trps1-Tg and double-Tg odontoblasts in comparison with WT and Dspp-Tg odontoblasts. This suggests that the Dspp-independent dentin mineralization defects in Trps1-Tg mice are a result of downregulation of a group of proteins critical for mineral deposition within the dentin matrix. In summary, by demonstrating that Trps1 functions as a repressor of later stages of dentinogenesis, we provide functional significance of the dynamic Trps1 expression pattern during dentinogenesis.